2021
DOI: 10.2196/26233
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Health Salt Reduction Intervention for People With Hypertension: Results of a Feasibility Randomized Controlled Trial

Abstract: Background A high-salt diet is a risk factor for hypertension and cardiovascular disease; therefore, reducing dietary salt intake is a key part of prevention strategies. There are few effective salt reduction interventions suitable for delivery in the primary care setting, where the majority of the management and diagnosis of hypertension occurs. Objective The aim of this study is to assess the feasibility of a complex behavioral intervention to lower s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 62 publications
0
48
0
Order By: Relevance
“…Of the 50 trials, 25 assessed the effects of the interventions among hypertensive participants [ 23 , 24 , 26 , 29 31 , 39 , 42 – 50 , 52 54 , 58 ], three among normotensive individuals [ 30 , 34 , 35 ], and 22 among both hypertensive and normotensive participants [ 21 , 22 , 25 , 27 , 28 , 31 , 33 , 36 38 , 40 , 41 , 51 , 55 57 , 59 , 60 ]. In 29 studies, BP was measured with an automatic sphygmomanometer, in five with a manual mercury sphygmomanometer [ 31 , 40 , 42 , 49 , 53 ], and six studies did not report BP measurement method [ 22 , 30 , 48 , 51 , 59 , 60 ]. Furthermore, in all the studies, BP measurement was performed by health professionals or trained personnel, with the exception of three studies that relied solely upon self-reported measures [ 34 , 35 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 50 trials, 25 assessed the effects of the interventions among hypertensive participants [ 23 , 24 , 26 , 29 31 , 39 , 42 – 50 , 52 54 , 58 ], three among normotensive individuals [ 30 , 34 , 35 ], and 22 among both hypertensive and normotensive participants [ 21 , 22 , 25 , 27 , 28 , 31 , 33 , 36 38 , 40 , 41 , 51 , 55 57 , 59 , 60 ]. In 29 studies, BP was measured with an automatic sphygmomanometer, in five with a manual mercury sphygmomanometer [ 31 , 40 , 42 , 49 , 53 ], and six studies did not report BP measurement method [ 22 , 30 , 48 , 51 , 59 , 60 ]. Furthermore, in all the studies, BP measurement was performed by health professionals or trained personnel, with the exception of three studies that relied solely upon self-reported measures [ 34 , 35 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in all the studies, BP measurement was performed by health professionals or trained personnel, with the exception of three studies that relied solely upon self-reported measures [ 34 , 35 , 47 ]. The included studies employed different types of intervention strategies that were categorized into four domains; 21 trials with nutritional education [ 21 , 28 , 31 , 38 , 40 – 42 , 46 , 49 , 50 , 52 , 55 , 56 , 59 61 ], 17 used salt substitutes [ 23 , 25 27 , 29 31 , 33 , 43 45 , 54 , 58 ], ten used self-help materials [ 34 37 , 39 , 47 , 48 , 51 , 53 , 57 ], and two trials employed food reformulation [ 22 , 24 ]. The control groups of all trials received usual care or no intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there is only one study available in the literature that evaluated the effect of an app intervention to reduce salt consumption using BCW; however, the study was focused on people with arterial hypertension and not on the general population [ 49 ].…”
Section: Discussionmentioning
confidence: 99%